AN ECOLOGICAL STUDY ON ALGAE IN ALTUN KUPRI DISTRICT – KIRKUK CITY/ IRAQ (British Journal of Global Ecology and Sustainable Development, 2022)
The current study was conducted to identify the algae present in the Lower Zab River within the Altun kupri district of Kirkuk Governorate, diagnose it, and determine the extent to which it is affected by the surrounding environmental factors. The two branches of the river and the rest of the stations are located between them. The study started from the month of November of the year (2021) and ended in the month of April of the year (2022).